PENGARUH VARIASI PENCAMPURAN JAMBU BIJI MERAH, ALPUKAT DAN WORTEL TERHADAP SIFAT FISIK, SIFAT ORGANOLEPTIK DAN KANDUNGAN GIZI PUDING LAPIS - Juni Gressilda Louisa Sine; Lilys Desyntia Bekak; Anita Sembiring; Asweros Umbu Zogara (Kupang Journal of Food and Nutrition Research, 2022)
Indonesia is a developing country that is experiencing changes in lifestyle in society, including changes in food consumption, this is at risk of causing degenerative diseases such as increased cholesterol.Fruits and vegetables contain many vitamins and minerals which are important nutritional components for the body of every human being, besides that they are also a good source of fiber for human digestion so that it can lower cholesterol levels. Research objectives  To identify the effect of variations in the mixing of red guava, avocado and carrot on the physical properties, organoleptic properties and nutritional content of layer pudding. Methods: This study was an experiment with a completely randomized design using 3 variations of a mixture of red guava, avocado and carrot. Then tested organoleptic to see the level of preference. The sample for the organoleptic test was 30 moderately trained panelists. The results showed the average organoleptic assessment of taste, color, aroma and texture in treatments P1, P2 and P3 with a liking category, except for color in P1 and P3 treatments with a very like category. Conclusion: There was no significant effect of mixing variations of red guava, avocado and carrot on the physical and organoleptic properties of pudding, while the addition of red guava, avocado and carrots affected the nutritional content of pudding. Of the three treatments that contained the most nutritional value of energy, protein and fat was in P1, the one containing the most nutritional value for carbohydrates was at P2, and the one containing the most nutritional value for fiber was at P3